The Relationship Between Family Income and Mother's Education Level and the Incidence of Stunting in Toddlers (Aged 24–59 Months) in the Working Area of Purwodadi 1 Public Health Center - Putri, Lena Siswanto; Firmansyah, Firmansyah (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Indonesia faces a triple burden of nutritional problems, including stunting, wasting, obesity, and micronutrient deficiencies such as anemia. Malnutrition occurs when individuals do not receive adequate intake of protein, energy, vitamins, and minerals, which can lead to stunting. Objective: This study aims to determine the relationship between family income and maternal education level with the incidence of stunting in toddlers in the working area of Purwodadi Community Health Center 1. Method: This observational study with a cross-sectional design involved 116 respondents. Data on family income and maternal education were collected through questionnaires and interviews, while toddler nutritional status was assessed through anthropometric measurements. Results: The majority of respondents had sufficient family income (54.3%), and most mothers had higher education levels (49.1%). Statistical analysis showed no significant relationship between family income and the incidence of stunting (p = 0.495). However, there was a significant relationship between maternal education level and the incidence of stunting (p = 0.006). Conclusion: Family income is not significantly associated with stunting incidence in toddlers, but maternal education level plays an important role in reducing stunting risk.